2005
DOI: 10.1051/vetres:2004059
|View full text |Cite
|
Sign up to set email alerts
|

The bovine viral diarrhea virus (BVDV) NS3 protein, when expressed alone in mammalian cells, induces apoptosis which correlates with caspase-8 and caspase-9 activation

Abstract: -The bovine viral diarrhea virus (BVDV) strains exist as two biotypes, cytopathic (cp) and noncytopathic (ncp), according to their effects on tissue culture cells. It has been previously reported that cell death associated to cp BVDV in vitro is mediated by apoptosis. Here, experiments were conducted to determine the involvement of the NS3 protein in the induction of apoptosis. The NS3-and NS3∆50 (deleted from the NH2-terminal 50 amino acids)-cDNA encoding sequences of BVDV NADL cp reference strain were cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
2
9
1
Order By: Relevance
“…Firstly, in the case of HCV, NS3 expressed in the absence of NS4A exhibits an aberrant subcellular localization (predominantly nuclear) and is rapidly degraded (half-life of 3 h), in comparison with NS3 expressed in the context of the NS3/4A complex (Wölk et al., 2000). Secondly, an N-terminal deletion of 50 residues had no effect on the ability of NS3 to induce apoptosis (St Louis et al, 2005), and, as previously demonstrated, such a deletion would be predicted to abolish protease activity . To clarify this situation, we used transient expression of wild-type and protease/helicase mutant derivatives of BVDV NS3, both alone and in the context of the NS2-3 fusion protein, which in all cases included NS4A.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Firstly, in the case of HCV, NS3 expressed in the absence of NS4A exhibits an aberrant subcellular localization (predominantly nuclear) and is rapidly degraded (half-life of 3 h), in comparison with NS3 expressed in the context of the NS3/4A complex (Wölk et al., 2000). Secondly, an N-terminal deletion of 50 residues had no effect on the ability of NS3 to induce apoptosis (St Louis et al, 2005), and, as previously demonstrated, such a deletion would be predicted to abolish protease activity . To clarify this situation, we used transient expression of wild-type and protease/helicase mutant derivatives of BVDV NS3, both alone and in the context of the NS2-3 fusion protein, which in all cases included NS4A.…”
Section: Discussionmentioning
confidence: 68%
“…not fused to NS2) is considered a marker of cytopathogenicity, it is not clear whether NS3 directly induces apoptosis. Previously, it was shown (St Louis et al, 2005) that BVDV NS3, expressed in the absence of NS4A from an adenovirus vector, and CSFV NS3 expressed as a green fluorescent protein fusion (Xu et al., 2007) were able to induce apoptosis. However, the physiological significance of these results is questionable for two reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…84 The viral protein NS3 induces apoptosis via activation of caspase 8 and the cytochrome c release-dependent caspase 9, thus inducing both extrinsic and intrinsic pathways. 140 Induction of moderate amounts of caspase 8 is associated with apoptosis of T-lymphocyte-rich interfollicular areas and marked apoptosis of B lymphocytes in lymphoid follicles during infection of ileal Peyer patches. 116 This finding suggests a role of the extrinsic pathway of apoptosis in gut-associated lymphoid tissue (GALT).…”
mentioning
confidence: 99%
“…3 Thus, the majority of the in vitro studies point to an involvement of the intrinsic rather than the extrinsic apoptosis pathway in cell death caused by cp BVDV infection. 14,37,48 However, it is still unclear if this mechanism also participates in the development of lesions present in animals dying of MD and whether it is correlated with BVDV antigen expression in vivo. The aim of this retrospective study was, therefore, to investigate the role of the various apoptosis pathways in the pathogenesis of lesions in animals suffering from MD.…”
mentioning
confidence: 99%